Influence of Heterologous and Homologous Vaccines, and Their Components, on the Host Immune Response and Protection Against Experimental Caprine Paratuberculosis - Arteche-Villasol, Noive; Gutiérrez-Expósito, Daniel; Elguezabal, Natalia; Sevilla, Iker A.; Vallejo, Raquel; Espinosa, José; Ferreras, María del Carmen; Benavides, Julio; Pérez, Valentín (Frontiers in Veterinary Science, 2022)
Vaccination against paratuberculosis, a chronic disease of ruminants caused by Mycobacterium avium subsp. paratuberculosis (Map), has been considered as the most effective control method. However, protection is incomplete, and the mechanisms operating in the response of the animals to vaccination are not fully understood. Therefore, this study analyzed the immune response and the effects on protection against Map infection, elicited by paratuberculosis (Silirum®) and tuberculosis (heat-inactivated M. bovis [HIMB]) vaccines and their components in a caprine experimental model. Fifty goat kids were divided into 10 groups (n = 5) according to their vaccination (Silirum®, HIMB and nonvaccinated), immunization (inactivated bacteria or adjuvant), and/or infection. Oral challenge with Map was performed 45 days postvaccination/immunization (dpv), and animals were euthanized at 190 dpv. Peripheral immune response and proportion of lymphocyte subpopulations were assessed monthly by enzyme-linked immunosorbent assay and flow cytometry analysis, respectively. Local immune response, proportion of tissue lymphocyte subpopulations, Map detection (polymerase chain reaction), and histological examination were conducted in gut-associated lymphoid tissues. All infected groups developed paratuberculosis granulomatous lesions despite vaccination or immunization. The Silirum® and HIMB-vaccinated groups showed a considerable lesion reduction consistent with a significant peripheral cellular and humoral immune response. Besides, a lower number of granulomas were observed in groups immunized with inactivated bacteria and adjuvants in comparison to nonvaccinated and infected group. However, despite not being significant, this reduction was even higher in adjuvant immunized groups, which developed milder granulomatous lesion with no detectable peripheral immune responses associated with immunization. No changes in the peripheral and local proportion of lymphocyte subsets or local immune response were detected in relation to either vaccination/immunization or infection. Despite that paratuberculosis and tuberculosis vaccination showed a partial and cross-protection against Map infection, respectively, only histological examination could assess the progression of infection in these animals. In addition, the pattern observed in the reduction of the lesions in adjuvant immunized groups suggests the possible involvement of a nonspecific immune response that reduces the development of granulomatous lesions.